KETAHANAN SEMAI AKASIA (Acacia mangium) PADA VARIASI UMUR TERHADAP INFEKSI Ganoderma spp. - Sulendra, Surya; Suryantini, Rosa; Wulandari, Reine Suci (Universitas Tanjungpura, 2017)
AbstractGanoderma is a pathogen cause rot root desease which attack the plant with a wide range of ages. It is necessary to do research to know level of acacia plant resistance at 1 month and 3 months on Ganoderma infection. The research aims was to determine the effect of Ganodermainfecton on acacia resistance at the age of 1 month and 3 month. The research used a factorial completely randomized design which consist of two treatment factor namely Ganoderma and age of seedling. Ganoderma treatment is control (G0), Ganoderma from palm oil (G1), Ganoderma from the acacia host (G2), Ganoderma from the rubber host (G3). The age treatment of seedling is 1 month acacia seedlings and 3 month acacia seedlings. Each treatment was repeated 3 times with 4 plants per replication resulting in 96 experimental units. Research observation variable is desease severty index by in vivo and dry weight of the plant. The result showed Ganoderma is pathogenic in 1 month acacia seedling with a severity index value of 0,6 and 3 month acacia seedling with a severity index value of 1. Dry weight of plant control treatment of acacia seedling age 3 months higher than other treatment that is 11,27. 3 month old acacia seedlings are more susceptible and rapidly cause symptoms of Ganoderma infection than 1 month old acacia seedlings.Â Keywords: Acacia mangium seedling, Ganoderma sp., In vivo Infection